PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA MARKETPLACE SHOPEE ( STUDI PADA PRODI MANAJEMEN MAHASISWA SEMESTER 8 UNIVERSITAS PAMULANG, TANGERANG SELATAN ) - Arief Maulana Sanny; Sugeng Widodo (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of product quality and promotion on customer loyalty in the Shopee marketplace (Study on the management study program of 8th semester students of Pamulang University, South Tangerang) both partially and simultaneously. The type of research in this writing is associative while the type of data in this study is quantitative. The sampling technique using random sampling obtained a sample in this study amounting to 100 respondents. The results of the study showed that product quality (X1) and promotion (X2) have a significant effect on customer loyalty (Y) with the regression equation Y = 2.284 + 0.564 (X1) + 0.610 (X2), The correlation coefficient value or level of influence between the independent variable and the dependent variable is obtained at 0.781 meaning that it has a strong relationship. The determination coefficient value of 0.702 means that the product quality and promotion variables have an effect on customer loyalty variables by 70.2% while the remaining 29.8% is influenced by other factors that were not studied. Hypothesis testing obtained the calculated F value > F table or (160,980 > 3.094), this is also strengthened by the p value < Sig. 0.05 or (0.000 < 0.50). Thus, H0 is rejected and H3 is accepted. This shows that there is a significant simultaneous influence between product quality and promotion on customer loyalty in the Shopee marketplace (Study on the management study program of 8th semester students at Pamulang University, South Tangerang).